Spontaneous haemoperitoneum with extravasation of contrast medium on CT due to bee sting vasculitis in a dog. Issue 4 (12th August 2021) - Colthurst, Stephanie Midori Margaret; Simcock, James Oliver; Kisielewicz, Caroline; Hodge, Priscilla; Rowan, Conor
Abstract: A 9‐year old female spayed Boston Terrier was found to have a bee stinger in the left metacarpal pad and subsequently collapsed. Treatment for anaphylaxis was initiated. Haemoperitoneum was diagnosed by abdominal focussed assessment with sonography for trauma (AFAST) and abdominocentesis. Computed tomography revealed extravasation of contrast medium indicating active haemorrhage. Exploratory coeliotomy and liver lobectomy were performed as there was concern by the attending clinicians that an underlying liver mass may be present due to evidence of active haemorrhage. Histopathology reported marked, acute, multifocal centrilobular and portal haemorrhage with no concurrent underlying pathology such as neoplasia. Subsequent interpretation of the CT by a boarded radiologist reported no clear cause for the haemorrhage. The multifocal extravasation of the contrast medium suggested a multifocal or diffuse haemorrhagic process. Vasculitis and coagulopathy secondary to bee‐sting was concluded. The dog recovered and follow‐up ultrasound 9 weeks later was unremarkable, supporting a one‐off event.